Chlorhexidine digluconate mouthwash alters the oral microbial composition and affects the prevalence of antimicrobial resistance genes - Bartsch, Sibylle; Kohnert, Eva; Kreutz, Clemens; Woelber, Johan P.; Anderson, Annette; Burkhardt, Ann-Sophie; Hellwig, Elmar; Buchalla, Wolfgang; Hiller, Karl-Anton; Ratka-Krueger, Petra; Cieplik, Fabian; Al-Ahmad, Ali (Frontiers in Microbiology, 2024)
Introduction: Chlorhexidine (CHX) is a commonly used antiseptic in situations of limited oral hygiene ability such as after periodontal surgery. However, CHX is also considered as a possible factor in the emergence of cross-resistance to antibiotics. The aim of this study was to analyze the changes in the oral microbiota and the prevalence of antimicrobial resistance genes (ARGs) due to CHX treatment.We analyzed the oral metagenome of 20 patients who applied a 0.2% CHX mouthwash twice daily for four weeks following periodontal surgical procedures. Saliva and supragingival plaque samples were examined before, directly after four weeks, and another four weeks after discontinuing the CHX treatment.Results: Alpha-diversity decreased significantly with CHX use. The Bray-Curtis dissimilarity increased in both sample sites and mainly streptococci showed a higher relative abundance after CHX treatment. Although no significant changes of ARGs could be detected, an increase in prevalence was found for genes that encode for tetracycline efflux pumps.Conclusions: CHX treatment appears to promote a caries-associated bacterial community and the emergence of tetracycline resistance genes. Future research should focus on CHX-related changes in the microbial community and whether the discovered tetracycline resistance genes promote resistance to CHX.